Design and analysis of hybrid electric multi-lobed airship for cargo transportation. (June 2022) - Manikandan, M.; Vaidya, Eshan; Pant, Rajkumar S.
Abstract: Though a lot of curiosity has been developed towards a sustainable mode of cargo transportation, multi-lobed hybrid airships are touted to be a viable alternative to the conventional aircraft. The advantages of these Lighter Than Air (LTA) vehicles can further be boosted by incorporating a renewable source of energy. The requirements of high power in cargo airships and the current technological barriers call for the development of a hybrid propulsion system that can couple the best of both conventional and electric propulsion. The electric propulsion system is established by integrating solar arrays with fuel cells, which is then combined with conventional engines in a parallel power train architecture ensuring minimum transfer of energy and compact size. A solar irradiance model is adopted, to evaluate the amount of energy generated by the solar arrays installed over the airship envelope. A multi-lobed hybrid airship model is presented whose aerodynamic characteristics are obtained using computational fluid dynamic tools, which are then utilized to evaluate the power requirements through flight performance analysis. The hybrid propulsion system is then modified in accord with the power needs of the hybrid airship. Finally, detailed weight distribution between hybrid-powered and conventional hybrid-airship is presented displaying significant reduction in fuel weight of ∼ 350 kg due to the hybrid propulsion system.